Tinjauan Desain Interface Website E-Commerce Wisata Mototravel.id Menggunakan Evaluasi Heuristik - Danang Tejo Kumoro; Uswatun Hasanah (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
This article is an overview of the website design interface of Lombok travel agencymorotravel.id. This review carried out using a heuristic evaluation introduced by Molich andNielsen that evaluates an interface in an information system. Heuristic evaluation is a guidethat can guide the design or used it as a tool for criticizing a decision taken. The aim is toimprove the model effectively. The evaluation includes visibility of system status, compatibilitybetween the system and the real world, control of user freedom, standards, and consistency,error prevention, user recognition of the system, flexibility and efficiency, aesthetic values andminimum values, system help, help features, and documentation. The purpose of thisevaluation is to measure morotravel.id's interface standard as one of the travel agent websitesin Lombok so that it can become a reference for information systems in the world of tourism.Based on the evaluation, it has stated that overall the morotravel.id site interface is feasible touse because it fulfills the completeness of the principles in the heuristic assessment. Still, ithas some things that need to be improved, especially in the help system and documentation.Heuristic evaluation is pragmatic and easy to do so that it gets quick results. Although thismethod does not produce high certainty, it is a relatively easy method to start an analysis ofinterface design. The hope for the next is the use of more than one way to improve the qualityof the analysis results because it meets the principle of complementarity in each evaluationmethod